NEED ASSESSMENT OF TEACHING QUALITATIVE RESEARCH IN UNDERGRADUATE MEDICAL EDUCATION: A MIXED METHOD STUDY - Adeeb, Humera; Qamar Naqvi, Syeda Saima; Ullah, Ihsan (Journal of Ayub Medical College Abbottabad, 2023)
Background: Accreditation bodies of medical education globally value competency in research that facilitates evidence-based practice of medicine. Physician-scientists need awareness of qualitative research methods for in-depth exploration of sociocultural, gender, behavioural, emotional, and religious factors affecting health that cannot be gauged by quantitative research methods. The introduction of qualitative research at the undergraduate level can enhance understanding of local populations’ unique health needs and strengthen evidence-based practice. Methods: This was a mixed-method study conducted from July to October 2021. Four journals with dedicated student’s corner/student journals were hand-searched for qualitative research articles published by students, over the past five years. Quantitative data was collected at four medical colleges of Khyber-Pakhtunkhwa for several qualitative research projects being conducted by students. Quantitative data was collected from the faculty of these colleges about the facilities of research departments. After analysing quantitative data, five semi-structured interviews via email were conducted about factors limiting qualitative research at medical colleges. Written responses were analysed for themes. Results: There was not a single qualitative research article published by students in local journals in five years. Out of 39 research projects by undergraduates at four medical colleges only one was qualitative. Two themes developed from qualitative data were underdeveloped research departments and a lack of attitude toward qualitative research. Conclusion: There is a felt need and gap to include qualitative research objectives at the undergraduate level, but before that emphasis needs to be placed on providing infrastructure, resources, and trained faculty to facilitate implementation. It will facilitate future doctors to find answers to problems impalpable by quantitative methods